Rancang Bangun Aplikasi Hybrid Kondisi Jalan dan Fasilitas Kelengkapan Jalan di Kota Mataram - Puspita Asri Nurmalasari; Nadiyasari Agitha; Ahmad Zafrullah Mardiansyah (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
Hybrid Application of Roads and Road Fittings Facilities Conditions in the City of Mataram is an application consisting of web applications and mobile applications. The web application is used by Dinas Pekerjaan Umum dan Penataan Ruang of mataram city and Dinas Perhubungan of mataram city to manage condition data from city roads and also road fittings facilities in the city of Mataram and to receive complaints of damage from the public. While the mobile application is used by the people of the city of Mataram to see the condition of the road and road fittings facilities based on data from the department and the public can also make complaints about damage from roads and road facilities. System testing using the Black Box method and MOS testing. MOS test results indicate that the average rating of respondents from Dinas Pekerjaan Umum dan Penataan Ruang of Mataram City stated strongly agree and agree were 66.67% and 33.33%. The average rating of respondents from Dinas Perhubungan of Mataram City stated strongly agree and agree were 58,33% and 41,67%. The average rating of respondents from the community stated strongly agree and agree were 52,50% and 44,17%. Therefore, this research concluded that this system is eligible to use.